Ursodeoxycholic acid protects against sepsis-induced acute kidney injury by activating Nrf2/HO-1 and inhibiting NF-κB pathway - Yunpeng Lou; Hongguang Shi; Ning Sha; Feifei Li; Xiaofeng Gu; Huiyan Lin (BMC Nephrology)
Abstract Background Ursodeoxycholic acid (UDCA), traditionally recognized for its hepatoprotective effects, has also shown potential in protecting kidney injury. This study aimed to evaluate the protective effects of UDCA against sepsis-induced acute kidney injury (AKI) and to elucidate the underlying mechanisms. Methods Sixty male C57BL/6 N mice were utilized to establish a sepsis-induced AKI model through intravenous injection of lipopolysaccharides (LPS, 10 mg/kg). UDCA (15, 30, and 60 mg/kg) was administered intraperitoneally once daily for 7 days before LPS injection. Kidney injury was evaluated by HE staining and biochemical markers, including serum creatinine (Cr), blood urea nitrogen (BUN), urinary protein, neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), N-acetyl-β-D-glucosaminidase (NAG), and retinol binding protein (RBP). Oxidative stress parameters and nuclear factor erythroid 2-related factor 2 (Nrf2)/ heme oxygenase-1 (HO-1) pathway, pro-inflammatory cytokines and nuclear factor-kappa B (NF-κB) pathway were also evaluated. Additionally, HK-2 cells were treated with LPS in vitro, and cell viability and apoptosis were detected using CCK-8 kit and flow cytometer, respectively. Results UDCA significantly attenuated LPS-induced renal histopathological damage and improved renal function, as evidenced by reduction in serum Cr, BUN, and urinary protein levels. UDCA also up-regulated the protein expression of zonula occludens-1 (ZO-1) and Ezrin in the kidney, and reduced the urinary levels of NGAL, KIM-1, NAG, and RBP. Moreover, UDCA inhibited NF-κB p65 phosphorylation and reduced pro-inflammatory cytokines levels (TNF-α, IL-1β, and IL-6) in both serum and kidney. UDCA alleviated oxidative stress by activating the Nrf2/HO-1 pathway in the kidney. In vitro, UDCA reduced LPS-induced cell injury and apoptosis in HK-2 cells, with these protective effects being blocked by the Nrf2 inhibitor ML385. Conclusions Our present study demonstrated that UDCA exerts protective effects against sepsis-induced AKI by attenuating oxidative stress and inflammation, primarily through the activation of the Nrf2/HO-1 pathway and inhibition of the NF-κB pathway. These findings highlight the therapeutic potential of UDCA in preventing sepsis-induced AKI.